Pour une analyse des textes iconiques en ethnologie - Gendreau, Andrée (Ethnologies, 1982)
AbstractThis article surveys the various currents in iconographie analysis as an aim to develop a general methodology that would take into account the specific phenomena related to traditional art forms.